1995
DOI: 10.1111/j.1432-1033.1995.0825a.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Influence of Calcium on the Heme Cavity of Cationic Peanut Peroxidase as Determined by 1H‐NMR Spectroscopy

Abstract: The cationic isozyme of peanut peroxidase (CPRx) is one of many peroxidases which requires calcium for enzyme activity. It has been previously shown that it requires 2 mol calcium to coordinate to 1 mol CPRx, and its related peroxidases from the basidiomycete Phanerochaete chrysosporium (Lip) and isozyme C of horseradish (HRPc). X-ray crystallographic studies of Lip have shown that calcium is ligated near the C-terminus of helices proximal and distal to the heme, where it has been suggested to maintain the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Horseradish peroxidase binds two Ca 2þ which are required to maintain the structural integrity of the heme, for which the geometry for catalysis is lost upon Ca 2þ removal (5,6). In cationic peanut peroxidase Ca 2þ is believed to position a catalytically important amino acid around the heme group which also affects the orientation of the porphyrin ring (7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Horseradish peroxidase binds two Ca 2þ which are required to maintain the structural integrity of the heme, for which the geometry for catalysis is lost upon Ca 2þ removal (5,6). In cationic peanut peroxidase Ca 2þ is believed to position a catalytically important amino acid around the heme group which also affects the orientation of the porphyrin ring (7).…”
Section: Discussionmentioning
confidence: 99%
“…Horseradish peroxidase binds two Ca 2+ which are required to maintain the structural integrity of the heme, for which the geometry for catalysis is lost upon Ca 2+ removal , . In cationic peanut peroxidase Ca 2+ is believed to position a catalytically important amino acid around the heme group which also affects the orientation of the porphyrin ring . For manganese peroxidase and lignin peroxidase it has been demonstrated that thermal inactivation which causes distinct alterations in the heme environment, change in heme spin state and changes in overall protein structure, is prevented and reversed in the presence of Ca 2+ , .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These Ca 2 + ions do not participate directly in the catalyzed reactions but are key player in supporting native protein structure, consequently guaranteeing the faultless activity and serviceability of enzymes. 5 The basic structural and functional connexions can be unleashed by exploiting the distinct properties of this enzyme making it a prototypical protein for conformational studies. It provides a proficient route for elimination of intracellular hydrogen peroxide from the region by catalyzing oxidation of an array of substrates by organic or hydrogen peroxides.…”
mentioning
confidence: 99%